ASSESSING THE INFLUENCE OF DIGITAL EXPERTISE, SOCIAL ENVIRONMENT AND LEADER TRUST ON PAI TEACHER ACHIEVEMENTS AS A STRATEGIC ASSET OF SCHOOL EXCELLENCE - Suci Hidayati; Siswanto Siswanto; Muhamad Walid; Obaidul Hoque (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
Today's society still assumes that teachers are the ones who are able to bring about major changes to educate the nation's children. One of these tasks lies on the shoulders of Islamic Religious Education (PAI) teachers who are expected to be able to form students with character by emphasizing Islamic values in behaving in their environment. Educational institutions will be of quality if the Human Resources in them have superior and quality competencies. This study aims to assess the extent of the influence of digital expertise, social environment and leader trust on improving the achievement of Islamic Religious Education (PAI) teachers in schools. The research method is quantitative descriptive with a sample of 110 respondents from PAI teachers in Malang Regency, using a Likert scale of 1-5. The results of the study obtained that (1) digital expertise has a significant effect on improving the achievement of PAI teachers by 0.014. (2) The social environment has a significant effect on improving the achievement of PAI teachers by 0.001 and (3) leader trust has not had a significant effect on improving the achievement of PAI teachers by 0.132. The three factors that are independent variables in this study prove that the achievement of Islamic Religious Education teachers increases if they have digital skills, a supportive social environment. The trust of leaders from the principal has only a slight and insignificant effect on the achievement of Islamic Religious Education teachers. The conclusion obtained is that the increasing achievement of Islamic Religious Education teachers can be one of the barometers of increasing the professionalism of Islamic Religious Education teachers with various competencies and skills they have, so that it has an impact on the quality of education and can become an asset of school excellence.